Pityriasis lichenoides-like mycosis fungoides. A case report. - Kavala, M.; Zindanci, I.; Sudogan, S.; Buyukbabani, N.; Kocaturk, E.; Can, B.; Turkoglu, Z. (European Journal of Pediatric Dermatology, 2010)
Mycosis fungoides represents the large majority of primary cutaneous T-cell lymphomas and usually begins as flat erythematous lesions. Pityriasis lichenoides (PL) is an idiopathic dermatosis consisting of recurrent crops of spontaneously regressing papules. Two clinical forms have been described. The acute form (PLEVA) is characterized by gross -5 to 15 mm in size- infiltrated lesions evolving into necrotic crusts, whereas the chronic form (PLC) is characterized by small scaly papules and macules. Cases with clinical features of pityriasis lichenoides together with histopathological findings of mycosis fungoides have been rarely described. We report an 8-year-old girl showing clinical features of PL, in whom the histological, immunohistochemical and T-cell receptor (TCR) rearrangement findings led to the diagnosis of mycosis fungoides.